Wall contrast enhancement of thrombosed intracranial aneurysms at 7T MRI - Sato, Taku; Matsushige, Toshinori; Chen, Bixia; Gembruch, O.; Dammann, P.; Jabbarli, R.; Forsting, M.; Junker, A.; Maderwald, S.; Quick, H.H.; Ladd, Mark E.; Sure, U.; et al. (American journal of neuroradiology, 2019)
BACKGROUND AND PURPOSE: The pathophysiology of wall contrast enhancement in thrombosed intracranial aneurysms is incompletely understood. This in vivo study aimed to investigate wall microstructures with gadolinium-enhanced 7T MR imaging. MATERIALS AND METHODS: Thirteen patients with 14 thrombosed intracranial aneurysms were evaluated using a 7T whole-body MR imaging system with nonenhanced and gadolinium-enhanced high-resolution MPRAGE. Tissue samples were available in 5 cases, and histopathologic ﬁndings were correlated with 7T MR imaging to identify the gadolinium-enhancing microstructures. - RESULTS: Partial or complete inner wall enhancement correlated with neovascularization of the inner wall layer and the adjacent thrombus. Additional partial or complete outer wall enhancement can be explained by formation of vasa vasorum in the outer aneurysm wall layer. The double-rim enhancement correlated with perifocal edema and wall histologic ﬁndings suggestive of instability. - CONCLUSIONS: Two distinct aneurysm wall microstructures responsible for gadolinium enhancement not depictable at lower spatial resolutions can be visualized in vivo using high-resolution gadolinium-enhanced 7T MR imaging.
Gesehen am 02.04.2020